Case Report: A case of cervical burkitt lymphoma and literature review - Miao, Sen; Bai, Yue; Hao, Hua (Frontiers in Oncology, 2026)
Primary cervical Burkitt’s lymphoma (BL) is an extremely rare malignancy. This report describes the case of a 55-year-old woman admitted to the hospital with irregular vaginal bleeding. Histologically, the tumor cells demonstrated infiltrative growth, relatively uniform basophilic cytoplasm. Immunohistochemical analysis revealed positivity for B-cell markers (CD20, CD79α, etc.), with MYC expression in approximately 80% of cells, fluorescence in situ hybridization staining showed positivity for MYC translocation and molecular testing confirmed IG rearrangement. The diagnosis of Burkitt’s lymphoma is based on its distinctive histological morphology in combination with immunohistochemistry and molecular testing.